SEARCH FOR STATE PARAMETERS OF THERMODYNAMIC MODELS OF GAS TURBINE SYSTEMS WITH DIFFERENT THRUST AMOUNTS - Лобунько, Олександр (SWorldJournal, 2024)
Individual values of working time and working conditions, thermal and technical condition of gas turbine systems may differ significantly from the indicators of the average statistical object. The paper considers modern approaches of thermodynamic modelin